Tea Trends in Latur City : Understanding Consumer Demands and Market Dynamics (International Journal of Scientific Research in Science and Technology, 2024)
This study examines the intricate relationship between consumer demands and market dynamics of the tea industry in Latur City. Through a comprehensive survey and analysis of socio-demographic variables, purchasing patterns, and preferences, this research aims to shed light on the key factors influencing tea consumption in the Latur city. Findings reveal a background shaped by cultural traditions, economic considerations, and the increasing influence of marketing strategies. Understanding these dynamics is critical for stakeholders in the tea industry to adapt their offerings and strategies to effectively meet the evolving needs of Latur’s tea consumers.